2018
DOI: 10.12659/msm.907032
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality of Life and the Need for Support for the Elderly with Good Physical and Mental Functioning

Abstract: BackgroundThe ageing of population is the reason that there are various strategies developed to help seniors acquire greater independence and a better quality of life. The aim of this study was to explore the relationship between the elderly peope’s need for assistance and assessed quality of life.Material/MethodsThe study included 100 participants who were members of a Seniors Club in Poznań, Poland. The cross-sectional study utilized the following instruments: Abbreviated Mental Test Score (AMTS), Instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
3
34
0
5
Order By: Relevance
“…The degree of capability in elderly subjects depends on the process of aging as well as on the comor- ). It was also found that the need for 24-hour care was significantly influenced by the following factors: urinary incontinence, difficulties in undertaking physical activity outside the home, depression, and oblivion [22]. Studies by Głowacka et al [23] indicate the conditioning of functional capacity of seniors at home by many factors, such as age, sex, education, place of residence, self-assessment of their own health, and housing with another family member.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of capability in elderly subjects depends on the process of aging as well as on the comor- ). It was also found that the need for 24-hour care was significantly influenced by the following factors: urinary incontinence, difficulties in undertaking physical activity outside the home, depression, and oblivion [22]. Studies by Głowacka et al [23] indicate the conditioning of functional capacity of seniors at home by many factors, such as age, sex, education, place of residence, self-assessment of their own health, and housing with another family member.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence is a condition which has a profound effect on wellbeing and quality of life of elderly people. (38)(39)(40) The International Continence Society has signified UI as a social problem. (41) In the present study 5.3% of the elderly people were having positive history of UI.…”
Section: Dementiamentioning
confidence: 99%
“…Many of the activities that commonly require assistance involve mental health and well-being, and they include staying healthy, getting around, seeing, hearing, and communicating. These are associated with quality of life, level of dependency, risk of falls, and the need for assistance [ 11 ]. Nunes et al further classified the needs of assistance into the following four categories: no need (requiring no caregiver), minimum need (requiring a caregiver sporadically), moderate need (requiring a caregiver intermittently), and maximum need (requiring a full-time caregiver).…”
Section: Introductionmentioning
confidence: 99%